Pengaruh Marketing Mix Dan Customer Shariah Relationship Marketing Terhadap Loyalitas Nasabah di BSM KC Krian - Muhammad Zainal Abidin (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This study aims to determine the effect of Marketing Mix on customer loyalty, Customer Shariah Relationship Marketing on Customer Loyalty and Marketing Mix and Customer Sahriah Relationship Marketing on Customer Loyalty.The result of this research is that Marketing Mix has a significant effect on Customer Loyalty, Costomer Shariah Relationship Marketing has a significant effect on Customer Loyalty and Marketing Mix and Customer Sahriah Relationship Marketing has a significant effect on Customer Loyalty.